Vulnerability Profile of Rural Households in South West Nigeria (2001)
This paper examined vulnerability to poverty of households among rural households in South West Nigeria using primary data from a two-wave panel survey (lean versus harvesting periods). Results showed that on the average there is a 0.56 probability of entering poverty a period ahead in the region and relatively high poverty rates were associated with much higher vulnerability while low poverty rates were associated with considerably low vulnerability. Vulnerable households are mostly large sized with high number of dependants and characterized by under aged or old, female headed, widowed household heads. They are mostly engaged in farming as their primary occupation, have no or low educational attainment and are landless. The findings underscore the centrality of social protection policy mechanisms as potent poverty reduction tools and necessary policy interventions to reduce consumption variability through reducing exposure to risk or improving the ex post coping mechanisms of the vulnerable.